Concomitant medications during immune checkpoint blockage in cancer patients: Novel insights in this emerging clinical scenario. (October 2019) - Rossi, Giovanni; Pezzuto, Aldo; Sini, Claudio; Tuzi, Alessandro; Citarella, Fabrizio; McCusker, Michael G.; Nigro, Olga; Tanda, Enrica; Russo, Alessandro
Abstract: The use of immune checkpoint inhibitors (ICIs) in cancer patients is rapidly growing. However, the potential impact of some widely used concomitant medications is still largely unclear. Emerging data suggest that gut microbiota may affect the efficacy of ICIs, leading to the hypothesis that concurrent antibiotics and proton pump inhibitors use could have a detrimental effect. In addition, steroid use might potentially impair the activity of immunotherapy, due its known immunosuppressive effects, and some safety concerns have been raised in patients receiving commonly used vaccination during ICIs. However, all randomized trials evaluating ICIs consistently excluded patients receiving high corticosteroid doses and data regarding other concomitant medications are lacking. Recently, several retrospective studies have tried to address this unmet medical need. Herein we discuss the latest evidence on the influence of these medications, critically analyzing the data reported so far and the possible implications in our clinical practice.